CITRA PEREMPUAN DALAM POLITIK - Tri Marhaeni Pudji (Yinyang: Jurnal Studi Islam Gender dan Anak, 2008)
Woman image in politic cant separated from woman social construct in social relation. This image in peopleâ€™s mind isstereotype and gender concept about woman in all sector, include in political and government sector, that woman â€œincapableâ€ to lead,because woman is irrational and rely on her emotion. Actually, thereâ€™s womanâ€™s chance to enter political domain, but itâ€™s very rare. Womanjustified as improper to politic because woman is kitchen/domestic â€œinhabitantâ€, irrational and nervous to take a risk. Thereâ€™s several factorthat influence emergence womanâ€™s leader, namely patriarchy culture, family relation, martyrdom, social class, lifestyle, social context, prisonexperience, and election system. Therefore, itâ€™s necessitating more woman candidate in political domain, objective recruitment process, andinitialized with quotaâ€™s system to create critical numbers of woman politicians